Towards Scalable Electroenzymatic Hydrogen Production with [FeFe]‐Hydrogenase - Sophie Webb; Ross D. Milton (ChemElectroChem)
Abstract The highly efficient [FeFe]‐hydrogenase enzyme could offer a new route to sustainable hydrogen (H2) production in the future, however key issues such as oxygen intolerance, structural fragility upon immobilization, as well as the need to produce the isolated enzyme in scalable quantities remains to be solved before this biotechnology becomes viable. This review touches upon some key issues which need to be addressed and provides a perspective on the future of electroenzymatic H2 production by [FeFe]‐hydrogenase.